2018
DOI: 10.1016/j.jcin.2017.06.060
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Body Mass Index on Clinical Outcomes in Female Patients Undergoing Percutaneous Coronary Intervention With Drug-Eluting Stents

Abstract: The risk of 3-year adjusted cardiac events did not differ across BMI groups, whereas the risk of all-cause mortality compared with normoweight was significantly higher in underweight patients and lower in overweight patients with a trend toward increased risk in the severely obese population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 29 publications
5
20
0
1
Order By: Relevance
“…First, currently, radial is the access of choice for the majority of the percutaneous coronary procedures, and thus the younger generation of interventional cardiologists are less experienced in managing femoral cannulation and its related complications [5,6]. Second, an increasing number of TFAs are used for high-risk patients undergoing complex PCvI and for the implantation of left ventricular devices; percutaneous aortic valve and endoprosthesis implantation require transfemoral access for bigger devices [14,[20][21][22]. Therefore, the magnitude of UGC benefits may potentially be greater in patients undergoing such high-risk interventions.…”
Section: Discussionmentioning
confidence: 99%
“…First, currently, radial is the access of choice for the majority of the percutaneous coronary procedures, and thus the younger generation of interventional cardiologists are less experienced in managing femoral cannulation and its related complications [5,6]. Second, an increasing number of TFAs are used for high-risk patients undergoing complex PCvI and for the implantation of left ventricular devices; percutaneous aortic valve and endoprosthesis implantation require transfemoral access for bigger devices [14,[20][21][22]. Therefore, the magnitude of UGC benefits may potentially be greater in patients undergoing such high-risk interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated an obesity paradox in patients with existing CAD after percutaneous coronary intervention (PCI) or coronary artery bypass grafting. These data are summarized in Table .…”
Section: Studies Showing An Obesity Paradox In Obese Compared With Nwmentioning
confidence: 99%
“…The 1‐year post‐PCI incidence of MACE and death was lower in overweight and obese than the underweight and NW patients (HR 0.71 [ P = .005] and 0.78 [ P = .056], respectively). Faggioni and colleagues examined the effects of obesity on cardiovascular mortality, all‐cause mortality, and MACE in 11 557 women aged 63 to 70 years with CAD. The patients were classified according to BMI as underweight (BMI < 18.5), NW (BMI 18.5–24.9), overweight (BMI 25–29.9), obese (BMI 30–34.9), or morbidly obese (BMI ≥ 35).…”
Section: Studies Showing An Obesity Paradox In Obese Compared With Nwmentioning
confidence: 99%
“…Тем не менее, в течение последних двух десятилетий были опубликованы результаты ряда исследований, в которых показано, что у паци-ентов с избыточным весом или ожирением может регистрироваться более благоприятный прогноз, чем у лиц с нормальным весом. Данный парадокс был описан у пациентов с различными заболеваниями [3], в том числе острым коронарным синдромом [4], чрескожными коронарными вмешательствами (ЧКВ) [5] и/или при инфаркте миокарда с подъемом сегмен-том ST (ИМпST) [6,7]. Единого мнения о причинах "парадокса ожирения" нет.…”
Section: результатыunclassified